Framing Pemberitaan Selebrasi Sujud Syukur Timnas Maroko Pada Nu Online - Auliya, Zuhal Ahsan; Ridwan, Aang; Rustandi, Ridwan (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2025)
This research aims to analyze the framing of NU Online’s coverage of the prostration of gratitude celebration by the Moroccan national team during the FIFA World Cup 2022 in Qatar, using the framing analysis approach developed by Robert N. Entman. The primary focus of this study is to understand how NU Online defines the event, identifies its causes, provides moral significance, and recommends actions regarding this prostration of gratitude. The methodology employed in this study is Entman’s framing analysis with a constructivist paradigm and a qualitative approach. Hence, this research is qualitative, with data collection techniques including non-participant observation and document study. Data analysis is conducted using a data analysis framework, followed by data validity techniques to ensure the accuracy of the results. The analysis results show that NU Online defines the prostration of gratitude as an expression of thanks to Allah for the victory achieved and as a manifestation of Islamic identity on the global stage. The cause of this celebration is identified as stemming from strong religious beliefs, while the moral significance emphasizes the importance of integrating worldly achievements with spirituality. Additionally, NU Online recommends that this act of prostration be set as an example for Muslims worldwide as a reminder of Allah's greatness in all aspects of life. The implications of this research include social aspects, highlighting diversity as framed by the media; academic aspects, contributing to the body of knowledge for similar studies; and practical aspects, serving as a means of da'wah (Islamic outreach) for journalists and other da'wah practitioners in applying gratitude to Allah SWT.